2013
DOI: 10.1016/j.ijgo.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

WHO recommendations for misoprostol use for obstetric and gynecologic indications

Abstract: The present comprehensive reference document was designed to enable clinicians and policy makers to quickly access and compare recommendations for the use of misoprostol in various reproductive health settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 13 publications
3
84
0
8
Order By: Relevance
“…The cervical ripening effect of misoprostol by different routes of administration has been demonstrated in labor, abortion induction and hysteroscopy [12,13,14]. Only a few studies have evaluated the use of misoprostol administered via different routes for women undergoing dilation and curettage.…”
Section: Introductionmentioning
confidence: 99%
“…The cervical ripening effect of misoprostol by different routes of administration has been demonstrated in labor, abortion induction and hysteroscopy [12,13,14]. Only a few studies have evaluated the use of misoprostol administered via different routes for women undergoing dilation and curettage.…”
Section: Introductionmentioning
confidence: 99%
“…Misoprostol can be applied by various routes and at various doses [6,12,24]. Because of its efficacy, cost-effectiveness, easy storage at room temperature and easy administration, misoprostol is listed as an essential medication by the World Health Organization [25,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…All studies have concluded that it is an effective medication for this indication [10][11][12]. WHO recommends that cervical ripening with misoprostol should have a maximum duration of 24 h [31]. To our knowledge, there is no study reporting on the incremental benefice of each additional misoprostol tablet and therefore on the optimal duration of misoprostol treatment for cervical ripening.…”
Section: Discussionmentioning
confidence: 99%